A 0.4–3-GHz nested bandpass filter and a 1.1–1.7-GHz balun bandpass filter using tunable band-switching technique. Issue 6 (4th May 2017) - Motoi, Keiichi; Oshima, Naoki; Kitsunezuka, Masaki; Kunihiro, Kazuaki
Abstract : This paper presents a second-order tunable single-ended (unbalanced) bandpass filter (BPF) with continuous 0.4–3-GHz coverage and a tunable balun BPF with continuous 1.1–1.7-GHz coverage for software-defined radio transceivers with the use of band-switchable and radio frequency (RF)-micro-electromechanical systems (MEMS)-tuned resonators. The BPFs are realized with two pairs of RF switches for coarse-tuning and RF-MEMS-tunable capacitors for fine-tuning. On the one hand, for the tunable single-ended BPF, a transition between three bands is enabled using two pairs of RF switches. On the other hand, for the tunable balun BPF, a transition between two bands is enabled using one pair of RF switches. Furthermore, the three-band switchable single-ended BPF is constructed in a nested two-filter bank structure for expanding the tuning range without increasing the footprint. In addition, to complement the discrete band gaps, RF-MEMS capacitor-tuned resonators are used, and a continuous tuning range of nearly the entire ultra-high-frequency band is achieved. The filter bank is fabricated on a Duroid substrate with εr = 3.5 and h = 0.787 mm. The filter bank has an insertion loss of 3.2–6.8 dB and a 1-dB bandwidth of 65–450 MHz with a continuous tuning range of 0.4–3 GHz.